Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-6 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Layout of the recording of single-nerve fiber action potentials to measure the self-organization of neuronal networks of the human CNS under physiologic and pathophysiologic conditions. By recording with two pairs of wire electrodes (B) from sacral nerve roots (cauda equina, C), containing between 200 and 500 myelinated nerve fibers, records were obtained in which single-nerve fiber action potentials (APs) were identified from motoneuron axons (main action potential (AP) phase downwards) and afferents (main AP phase upwards).